2021
DOI: 10.3988/jcn.2021.17.3.419
|View full text |Cite
|
Sign up to set email alerts
|

The Ruminative Thought Style with Associated Anxiety Influences the Occurrence of Medication-Overuse Headache

Abstract: Background and Purpose To determine the relationships between the ruminative thought style, parameters of psychological distress, and the occurrence of medication-overuse headache (MOH). Methods The study included 164 subjects: 83 patients (11 males and 72 females) who were first diagnosed as MOH, and 81 healthy subjects (22 males and 59 females) as a control group (CG). The study participants were aged 40.2±11.9 years (mean±standard deviation), and they were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The average age of the study subjects was 40.2 ± 11.9 years (min 18, max 71 years). Data in details are described in our previous published paper [15]. All SF-36 scores (PCS, MCS, TS) were statistically significantly lower in MOH compared to the CG (p <0.001).…”
Section: Resultsmentioning
confidence: 85%
“…The average age of the study subjects was 40.2 ± 11.9 years (min 18, max 71 years). Data in details are described in our previous published paper [15]. All SF-36 scores (PCS, MCS, TS) were statistically significantly lower in MOH compared to the CG (p <0.001).…”
Section: Resultsmentioning
confidence: 85%
“…A follow-up study has observed that central sensitization is Genetic studies suggest the possible importance of polymorphisms in genes relate to the dopaminergic system (DRD4, DRD2, and SLC6A3) and genes involved in th neurobiology of the addiction syndrome (WSF1, BDNF, ACE, and HDAC3) [11] (Figur 1). Central sensitization plays a key role in the pathophysiology of chronic migraine [44 Analysis of somatosensory evoked potentials has shown that patients with chroni Functional neuroimaging studies have shown functional changes in regions involved in nociceptive processes, such as the mesolimbic reward system, the fronto-parietal system, and other regions [53,54]. The mesolimbic system consists of the ventromedial prefrontal cortex, the accumbens region, the substantia nigra, and the ventral tegmental area, which show altered functions in MOH.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Functional neuroimaging studies have shown functional changes in regions involved in nociceptive processes, such as the mesolimbic reward system, the fronto-parietal system, and other regions (53,54). The mesolimbic system consists of the ventromedial prefrontal cortex, the accumbens region, the substantianigra, and the ventral tegmental area, which show altered functions in MOH.…”
Section: Figurementioning
confidence: 99%